2004
DOI: 10.1074/jbc.m402395200
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-mediated Cleavage of Insulin Receptor Substrate

Abstract: Apoptosis is an important mechanism for maintaining tissue homeostasis. The efficient induction and execution of apoptosis are essential for cell clearance in specific developmental situations. Insulin-like growth factor (IGF)-I is a survival factor for epithelial cells in the mammary gland, and its withdrawal or inhibition leads to apoptosis. In this paper we describe a novel mechanism that may lead to suppression of an IGF-I-mediated signaling pathway through cleavage of insulin receptor substrate (IRS). Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…116 The dramatic changes in IRS protein levels occurred in the absence of any alteration in mRNA levels, indicating that this effect was post-transcriptional. 115 While we don't know the mechanisms of loss of IRS proteins during involution, Dr Streuli's group has shown that this maybe mediated by caspase 10 degradation, 117 and our studies would suggests that it maybe via proteasomal degradation. 110 We have performed limited experiments to assess IRS activity during mammary gland development.…”
Section: Irss In Mammary Gland Development and Functionmentioning
confidence: 99%
“…116 The dramatic changes in IRS protein levels occurred in the absence of any alteration in mRNA levels, indicating that this effect was post-transcriptional. 115 While we don't know the mechanisms of loss of IRS proteins during involution, Dr Streuli's group has shown that this maybe mediated by caspase 10 degradation, 117 and our studies would suggests that it maybe via proteasomal degradation. 110 We have performed limited experiments to assess IRS activity during mammary gland development.…”
Section: Irss In Mammary Gland Development and Functionmentioning
confidence: 99%
“…The resulting reactant (9 l) was incubated with 50 ng of recombinant caspase-3 in the presence or absence of 50 M Z-VAD-fmk (a pan-caspase inhibitor) in 20 l of caspase reaction buffer (50 mM HEPES, 50 mM NaCl, 0.1% CHAPS, 10 mM EDTA, 5% glycerol, 10 mM dithiothreitol, pH 7.2) for 1.5 h at 37°C (28). To examine the specificity of caspase-3-mediated cleavage, the metabolically labeled mouse anamorsin wild type was incubated with 50 ng of recombinant human caspase-2, -7, and -8 (R&D Systems, Minneapolis, MN) or recombinant human caspase-6 and -9 (Enzo Life Sciences, Plymouth Meeting, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Although some reports have implicated caspase-10 in apoptosis of murine cells, [25][26][27] there is clear evidence that the caspase-10 gene is absent in the mouse genome. 28,29 Therefore, we wondered whether paclitaxel could induce apoptosis in murine cells or, alternatively, trigger other death mechanisms.…”
Section: Mefs Devoid Of Caspase-10 Are Sensitive To Paclitaxel-inducementioning
confidence: 99%